Prayer and Ethics in the Sermon on the Mount - Troftgruben, Troy M. 1976- (2020)
Two parts of the Christian life as seen in the Sermon on the Mount are spiritual practices and service to one’s neighbor. Though these two are often separated, this discourse shows that they are in fact interrelated, and that each depends on the other for strength and focus.